Genetic Diversity Analysis and Development of DNA Fingerprints of 20 Indonesian Local Chili Pepper Varieties Based on SSR Markers - Rerenstradika Tizar Terryana; Nadia Della Savitri Ayu Ningrum; Kristianto Nugroho; Darmawan Saptadi; Helmi Kurniawan; Puji Lestari (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2020)
Chili pepper is one of the most valuable horticultural crops, widely cultivated in Indonesia. Analysis of its genetic diversity is needed to develop successful breeding programs of local varieties. Simple sequence repeat (SSR), a robust molecular marker used for genetic diversity analysis in plant species, offers potential, reliable DNA fingerprinting method to assess genetic variation and varietal identification of chili pepper. Fifteen SSR markers were used in this study to analyze the genetic diversity and develop profiling identification of DNA fingerprint of local chili pepper varieties. Twenty local and two improved varieties of three chili pepper species, consisting of 3, 1, and 18 varieties of Capsicum frutescens, C. chinense, and C. annuum, respectively, were assessed for their SSR polymorphism. A total of 87 alleles was obtained from the polymorphism analysis with high alleles variation (2–16 alleles) with average total allele of 5.8 and average polymorphism information content (PIC) of 0.59 (0.34–0.83). Clustering and Principle Coordinate Analyses (PCoA) classified the varieties into two groups with coefficient of similarity of 0.65 indicating their high genetic variability. Most local varieties belonged to the same cluster and separated from the two improved varieties. Based on PIC values and dendrogram with selected markers, five SSR markers, i.e. EPMS441, EPMS331, EPMS335, GPMS194, and CaSSRBio1.1, were identified as SSR marker set for DNA fingerprinting purposes. SSR marker set used in this study was successful in developing the varietal identity of local chili pepper varieties, as indicated by unique code of each variety.